A Comprehensive Review of the Functionalized Integrated Application of Gel Polymer Electrolytes in Electrochromic Devices - Xu, Lei; Zhang, Leipeng; Liu, Dongqi; Ren, Zichen; Liu, Wenchao; Zhang, Yike; Wang, Yuqiang; Sun, Jiawu; Yang, Rui; Lv, Zekuo; Zhao, Jiupeng; Li, Yao (Nano-Micro Letters, 2026)
With the global push for energy conservation and the rapid development of low-power, flexible and wearable optical displays, the demand for electrochromic technology has surged. Gel polymer electrolytes (GPEs), a crucial component of electrochromic devices (ECDs), show great promise in applications. This is attributed to their efficient ion-transport capabilities, excellent mechanical properties and strong adhesion. All of these characteristics are conducive to enhancing the safety of the devices, streamlining the packaging process, significantly improving the electrochromic performance of ECDs and boosting their commercial application potential. This review provides a comprehensive overview of GPEs for ECDs, focusing on their basic designs, functional modifications and practical applications. Firstly, this review outlines the fundamental design of GPEs for ECDs, encompassing key performance index, classification, gelation mechanism and preparation methods. Building on this foundation, it provides an in-depth discussion of functionalized GPEs developed to enhance device performance or expand functionality, including electrochromic, temperature-responsive, photo-responsive and stretchable self-healing GPE. Furthermore, the integration of GPEs into various ECD applications, including smart windows, displays, energy storage devices and wearable electronic, are summarized to highlight the advantages that the design of GPEs brings to the practical application of ECDs. Finally, based on the summary of GPEs employed for ECDs, the challenges and development expectations in this direction were indicated. Highlights: 1 In response to the demands of electrochromic devices, the advantages and designs of the corresponding multifunctional integrated gel polymer electrolytes were discussed. 2 Through reviewing the applications of electrochromic devices based on gel polymer electrolytes, the remarkable advantages that gel polymer electrolytes bring to electrochromic devices and their practical applications in electrochromic devices were analyzed. 3 The future research directions of gel polymer electrolytes for electrochromic devices were explored, thereby facilitating their further development and commercial application.